« Appartenir aux classes populaires » : L’exemple du pub dans l’Angleterre victorienne - Isabelle Cases (Cahiers Victoriens et Edouardiens)
In the Victorian period, the public house gradually replaced the former beer shops and gin palaces. At the same time the middle classes began to turn away from the pub, which they did not consider respectable enough, and which therefore became an almost exclusively lower-class institution. Nevertheless segregation and a certain hierarchy did not disappear from the pub, the architecture of which very often perpetuated a very complex social stratification. Though popular groups developed in many ways a strong sense of belonging in their local pub, a lot of people found themselves caught up in a complex commercial, social and moral structure, which they did not always perfectly understand or control.